KH. MUHAMMAD HARUN NAFSI DALAM PEMBINAAN KEAGAMAAN DI SAMARINDA - Samsir Samsir (JSI: Jurnal Sejarah Islam, 2022)
This study is entitled "The Role of KH. Muhammad Harun Nafsi In Religious Coaching of Samarinda City ". Background Coaching is basically a conscious effort carried out by planned to improve the atmosphere of a better life and in accordance with the teachings of the Islamic religion. Coaching that should be done continuously so as to get what is expected is a safe, peaceful, happy, prosperous life and get the pleasure of Allah SWT. The purpose is to find out how the role of KH. Muhammad Harun Nafsi in religious formation in the city of Samarinda. This type of research is a qualitative description that explains in more detail through in-depth analysis of the subject under study. The study used field research using a qualitative descriptive approach. The location of this research is in Samarinda. Data collection techniques include observation, interviews and documentation. The data analysis technique used is descriptive analysis. The results of this study are KH. Muhammad Harun Nafsi, founded a HEP Cokroaminoto SMEP and Middle School, Islamic boarding school and a school called At-Taqwa Harun al-Rasyid, better known by the local community as "Arab School" in 1977. As a preacher acted by KH. Muhammad Harun Nafsi preached to Sangkulirang. Forming the majelis ta ‟lim located in his own home on Jalan Cokroaminoto, Samarinda Seberang. The Ta‟ lim assemblies were attended by the community around KH. Harun Nafsi. This assembly is usually called "Assembly of the Village.